Tuloy Baguio cultural & livelihood complex - Ledda, Kristine Mae D.
Addressing Baguio City's existing cultural heritage from the city's indigenous ancestry and thriving opportunity in terms of economic growth, the primary agenda of the proposed project, Tuloy : Baguio Cultural & Livelihood Complex, is to support its cultural preservation within the community as well as to promote its tradition as part of Cordillera through showcasing its cultural heritage while sustaining the community's traditional livelihood such as weaving, painting, wood carving, and sculpting through education and world-wide engagement. These agenda further translate to the project's title "Tuloy" which serves as the root word of two Tagalog terms : tumuloy which means [1] to welcome tourists and local entrepreneurs and ipagpatuloy which means [2] to continue the cultural preservation and traditional livelihood activities. Its location as Cordillera's prime city and continuous growth in terms of tourism has supported its culture and economy through tourism, education, and livelihood engagements that strengthen its neighborhood as well as its built environment. Thus, making it a gateway for the development of education, tourism, and expansion of business trades.